Cell Surface Processing of CD109 by Meprin β Leads to the Release of Soluble Fragments and Reduced Expression on Extracellular Vesicles - Lückstädt, Wiebke; Bub, Simon; Koudelka, Tomas; Pavlenko, Egor; Peters, Florian; Somasundaram, Prasath; Becker-Pauly, Christoph; Lucius, Ralph; Zunke, Friederike; Arnold, Philipp (Frontiers in Cell and Developmental Biology, 2021)
Cluster of differentiation 109 (CD109) is a glycosylphosphatidylinositol (GPI) anchored protein expressed on primitive hematopoietic stem cells, activated platelets, CD4+ and CD8+ T-cells and keratinocytes. In recent years CD109 was also associated with different tumor entities and identified as a possible future diagnostic marker linked to reduced patient survival. Also, different cell signaling pathways were proposed as targets for CD109 interference including the TGFβ, JAK-STAT3, YAP/TAZ and EGFR/AKT/mTOR pathways. Here, we identify the metalloproteinase meprin β to cleave CD109 at the cell surface and thereby induce the release of cleavage fragments of different size. Major cleavage was identified within the bait region of CD109 residing in the middle of the protein. To identify the structural localization of the bait region, homology modeling and single particle analysis were applied, resulting in a molecular model of membrane associated CD109, which allows for the localization of the newly identified cleavage sites for meprin β and the previously published cleavage sites for the metalloproteinase bone morphogenetic protein 1 (BMP-1). Full-length CD109 localized on extracellular vesicles (EVs) was also identified as a release mechanism and we can show that proteolytic cleavage of CD109 at the cell surface reduces the amount of CD109 sorted to EVs. In summary, we identified meprin β as the first membrane bound protease to cleave CD109 within the bait region, provide a first structural model for CD109 and show that cell surface proteolysis correlates negatively with CD109 released on EVs.